Comparative Study of Adaptive Multivariate EWMA Control Charts - Lee, Ming Ha (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
The purpose of this study is to compare the optimal statistical performances among the adaptive multivariate exponentially weighted moving average (MEWMA) control charts, i.e. variable sample sizes (VSS) chart, variable sampling intervals (VSI) chart, and variable sample sizes and sampling intervals (VSSI) chart. It is shown that the optimal VSI and VSSI MEWMA charts are more efficient than the optimal VSS MEWMA chart for detecting shifts in the process mean vector. In addition, it is also shown that all the optimal adaptive MEWMA charts perform better than the corresponding fixed sampling rate (FSR) MEWMA chart for detecting shifts in the process mean vector.